PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II SDN 006 TRI MULYA JAYA KECAMATAN UKUI - ', Murjiyem (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low results of social studies grade II SDN 006 Tri MulyaJaya. Of the 20 students, only 9 students (45.00%) who completed study results. In additionthe average learning result by 50. This research aims to improve student learning outcomesthrough the application of IPS CTL approach. This research is a classroom action research(CAR) conducted by two cycles. The data used in this study is the result of learning andactivity data of teachers and students. Research suggests that the approach applied setelahalearning outcomes and data CTL activity of teachers and students has increased. Datateacher activity increased in each cycle, the first cycle of the first meeting activity for teachersto get a score of 22 (50.00%) with less category, the first cycle II meeting teacher activityincreased with the acquisition of a score of 27 (61.36%) by category enough, in the secondcycle the first meeting back teacher activity increased with the acquisition of a score of 34(77.27%) in both categories. And the second cycle II meeting teacher activity increased with ascore of 39 (88.64%) with a very good category. Additionally the activity of students hasincreased at each meeting in each cycle. At the first meeting of the first cycle of activitystudents obtain a score of 21 (47.73 %%) with less category, the second meeting of the secondcycle increased student activity with a score of 25 (56.82%) with enough categories, the firstmeeting of the second cycle of activity students experience an increase in the acquisition of ascore of 35 (79.55%) in both categories. And at the second meeting of the second cycle ofstudent activity increased with the acquisition of a score of 37 (84.09%) with a frighteninggood category. Learning outcomes UH I and II increased from a base score, as evidenced bythe thoroughness of learning outcomes IPS in the first cycle of individual 14 students (70%)were completed and six students (30%) who did not complete. In the second cycle increasedto 16 students (80%) were completed while 4 students (20%) did not complete.